Phenomenon Wind Direction and Speed Based on Cloud Movement As an Early Warning Related to the Destructive Wind - Tri Harsono,Achmad Basuki,Taufiqurahman,Nailussa’ada (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Wind is the flow of gases on a large scale. On the surface of the Earth, wind consists of the bulk movement of air. In meteorology, winds are often referred to according to their strength, and the direction from which the wind is blowing. There are some severe wind that can cause tremendous physical destruction, injury, loss of life and economic damage, such as tornado, wind shear, cyclone or typhoon. In Indonesia itself there are more than 600 tornados during 2017. The prediction and detection about wind movement direction and speed is required, it can be used as important information to the related institution for early warning with respect to the existence of wind that can damage physical buildings and endanger human lives. This study concerned to the phenomenon of the winds speed and direction that be observed from the cloud movement in the one image to the next based on geostationary satellite imagery from the Himawari 8-IR Enhanced that provided by Indonesian agency for meteorology, climatology and geophysics. Clustering process was used to segmenting each cloud type and produces the centroid point. The movement of each centroid in every sequential image was measured and analyzed to become the result of wind speed and direction. This wind information especially direction and speed is useful to recognize the symptom of each wind phenomenon.